Some Remarks on Criminology and Moral Philosophy. Issue 3 (2nd September 2019) - Jacobs, Jonathan
Abstract : Recent developments in philosophy and in criminology indicate that there are significant respects in which the two disciplines can be mutually informing. Many philosophers are increasingly interested in exploring empirical aspects of philosophical claims, and criminologists are finding their way past the alleged fact/value distinction and are rediscovering the moral significance of facts, especially regarding punishment and desistance. In some recent criminological studies there are implicit links to the British moralists such as David Hume and Adam Smith, and to Aristotle as well. This paper explicates those links and some of the possibilities for philosophy and criminology to be mutually informing.